(untitled) (Malaysian Journal of Civil Engineering, 2018)
Subgrade of a pavement should be strong enough to give adequate support to the pavement and for supporting and distributing the wheel loads. The design and behaviour of a flexible pavement depends mainly on the stability of the subgrade soil, which can be increased by compacting the soil at optimum moisture content (OMC) thus achieving maximum dry density (MDD). In this study, Modified Proctor Compaction Test (MPCT) was conducted by giving 5 different number of blows per layer so as to establish a relationship of compaction energy with OMC & MDD. Also, OMC and MDD are one of the most important parameters influencing California Bearing Ratio (CBR) test. CBR is a penetration test used for evaluating the mechanical strength of subgrade soil and for determining the thickness of the pavement required. Determination of soaked and unsoaked CBR value for a soil is time consuming and a laborious process. Hence in this paper an attempt has been made to arrive at regression equations to correlate soaked and unsoaked CBR values for the silty clay (CL) soil with the compaction characteristics, so that based on OMC and MDD, CBR value of soil can be predicted thus avoiding the time consuming process of conducting CBR tests. The soil sample used in this project was a disturbed sample collected from Thiruporur District in Chennai.